Supervised resistance training in an individual with glioblastoma undergoing chemoradiation: a case report - Nakfoor, Bruce; Fairman, Ciaran M. (Frontiers in Oncology, 2026)
IntroductionExercise has demonstrated safety and efficacy in mitigating treatment-related symptoms across cancer populations; however, evidence in neuro-oncology remains limited, particularly during active chemoradiation.MethodsWe report the case of a 63-year-old individual with newly diagnosed glioblastoma, experiencing symptoms of fatigue, balance issues, headaches, and memory loss, who initiated a 12-week supervised resistance training program during concurrent chemoradiation. Assessments at baseline and post-intervention included physical function and quality-of-life outcomes.ResultsAdherence was 56% (20/36 sessions), and no adverse events occurred. The patient showed improvements in 6-minute walk distance and short physical performance battery score that exceeded established minimal clinically important differences. Quality-of-life findings were mixed, with certain domains benefiting from the exercise intervention and others worsening.DiscussionThis case highlights the feasibility and safety of supervised resistance training during active glioblastoma chemoradiation. The observed improvements in physical function and select quality-of-life domains represent exploratory signals that compare favorably with the extant exercise oncology literature.